Application methods influence biochar–fertilizer interactive effects on soil nitrogen dynamics. Issue 6 (12th January 2021) - Li, Xiuwen; Neupane, Avishesh; Xu, Sutie; Abdoulmoumine, Nourredine; DeBruyn, Jennifer M.; Walker, Forbes; Jagadamma, Sindhu
Abstract: The potential nitrogen (N) losses from soils with fertilizer addition can be reduced when biochar is co‐applied, but this effect is influenced by the methods of biochar and fertilizer application. In a 60‐d laboratory incubation experiment, we investigated how two fertilizer application methods (surface placement and soil incorporation) affected N transformation in soils under the following treatments: control (soil with no biochar and urea [C]), biochar (150 mg N g −1 soil [B]), urea (150 mg N g −1 soil [U]), and the combination of B + U (75 mg N g −1 soil each B and U). Our results showed that at Day 30, the concentrations of soil NH4 + –N and NO3 − –N remained significantly higher for U but were relatively similar to control for biochar‐included treatments, indicating that the presence of biochar slowed the mineralization of urea during that period. The concentration of soil NO3 − –N and cumulative N2 O production under B + U treatment at 60 d was around two times higher for incorporation treatment compared with the surface treatment, indicative of a longer‐term N regulatory effect of biochar with the surface application method. Additionally, we observed a higher number of amo A gene transcripts when B + U was incorporated in the soil compared with applied to the surface at the later stage of incubation, indicative of higher potential nitrification activity. These results suggest that the surface application of B + U can be used as a slow release N source that can provide long‐term N supply to the crops, while the soil incorporation method could be used for crops that need low N at the beginning of the growth but require a substantial amount of it later. Surface co‐application of B + U can also be a good strategy to reduce soil N losses by slowing down ammonification, nitrification, N2 O emission, and ammonia oxidizing bacteria activity.